Development of an innovative clinical pharmacy service in a urology surgical unit: a new initiative from Qatar - Lina Naseralallah; Somaya Koraysh; Nour Isleem; Afif Ahmed; Moza Al Hail (Taylor & Francis Group, 2024)
Purpose To provide an insight into the role of a clinical pharmacy initiative in a surgical urology unit through evaluating the nature, significance, associated medications, and acceptance rate of pharmacist interventions.Methods A cross-sectional study was carried out at the Ambulatory Care Center (ACC), Doha, Qatar. Data related to clinical pharmacist interventions and associated rationale were classified according to the nature of the intervention using an adapted classification system. The assessment of the severity followed the National Patient Safety Agency (NPSA) Risk Matrix. Linear regression, Kruskal-Wallis, and post-hoc analyses were performed to determine the association between patient-related and medication-related characteristics on pharmacist interventions.Results A total of 3284 interventions (on 1486 patients) were analysed. Most patients (n = 1105; 74.4%) had 1-2 interventions. Age and gender showed a positive linear correlation with the number of interventions per patient (p < 0.01). Majority of interventions were related to pharmacological strategy (n = 1858; 56.6%) and quantity of drug (n = 821; 25%). Additional drug therapy (n = 748; 22.78%) was the most common subcategory followed by optimum dose/frequency (n = 691; 21.04%) and discontinuation of medications (n = 352, 10.72%). Anti-infectives were the most identified drug category (n = 798, 55.1%). Most interventions (59.4%) were of moderate significance; patients with moderate interventions were found to be older compared to patients with minor interventions (p = 0.032). Prescribers' acceptance rate was high (>90%), with a notable increase of 6.6% from 2021 to 2023.Conclusion This study showed that the clinical pharmacy service in the urology surgical field was a fruitful initiative. The clinical pharmacist's role has expanded to include not only therapeutic optimisation while ensuring medication safety across the continuum of perioperative care but also the identification and management of untreated health problems. The dynamic and complexity of the urology patient population challenge clinical pharmacists; however, the practice concepts remain the same as in any other clinical setting.